The Prototype of Ebod Jaya Online M-Commerce Application - Hamdani, Dani; Amalia, Endang; Mardiana, Siti (International Journal of Psychosocial Rehabilitation, 2020)
Indonesian people are people who cannot be separated from the use of smartphones. M-commerce is a sale and purchase transaction using a smartphone. Currently, in Indonesia, the number of chirping fans has increased quite significantly. This opens up very promising business opportunities. Ebod Jaya Factory is a factory that provides for bird feed, medicine, vitamins, bird cages, and accessories. The system development method used is prototyping. The results of this study are in the form of a prototype m-commerce application for the sale of products manufactured by the Ebod Jaya factory.